Ethnobotanical survey of Olea europaea L. subsp. europaea var. sylvestris (Mill.) Lehr (Oleaster) in the Fez–Meknes Region (Morocco): Traditional knowledge, uses, and conservation insight - Maai, Mohamed; Zahir, Ilham; Nissmouya, Amal; Moubchir, Tarik; Sakar, El Hassan (Ethnobotany Research and Applications, 2026)
Background: This study investigates traditional uses and local knowledge of wild olive (Olea europaea L. subsp. europaea var. sylvestris (Mill.) Lehr), commonly known as oleaster, in traditional medicine, agriculture, food, and other local practices in Fez–Meknes region of Morocco. Methods: From October 2023 to January 2025, an ethnobotanical survey was carried out in the Fez–Meknes area using a structured questionnaire. A total of 420 informants were interviewed to document knowledge and uses of oleaster.The Chi-square test and Factorial analysis were used to explore and visualize associations between variables and identify profiles of knowledge and practices. Results: The survey shows that traditional knowledge and use of oleaster are mainly preserved by older people (>60%), rural residents (56%), low-education groups (57%), and married individuals (55%). Therapeutic uses dominate (30.5%), followed by agricultural uses (28.6%). In traditional medicine, oleaster is often used to treat oral problems (33.72%), diabetes (15.12%), and gastro-duodenal disorders (6.28%). In agriculture, it is mainly used as a rootstock (35.63%). Leaves are primarily employed for therapeutic purposes (55.3%), while the whole plant is used in agriculture (64.3%), fruits are favored in cosmetics (76.1%) and cooking (95%). Dosage is imprecise and toxicity is rare with minor side effects reported. Conclusions: This study confirms a multifield important interest (mainly medicinal) of the oleaster in Fez-Meknes (Morocco). Further research should validate its medicinal properties, encourage safe use, and preserve such knowledge. Keywords: medicinal plants, indigenous practices, rural communities, health disorders, toxicity